Intention of Basic Technology Teachers on The Use of ICT for Teaching in Ilorin Metropolis - Kehinde Muritala Nuhu; Gboyega Ayodeji Aladesusi (Indonesian Journal Of Educational Research and Review, 2022)
Educational systems around the world are becoming increasingly pressured to apply the new ICT tools to their curriculum to provide students with the knowledge and skills that they need in the 21st century. This study analyses the intention of Basic Technology teachers on the use of ICT for teaching. The study was a descriptive of survey type. A total no of 270 respondents are the sample for the study. Data were collected using structured questionnaire. Descriptive statistics was used to answer the research questions; hypothesis was tested with independent t-test. The findings of the study were that; Basic Technology teachers agreed to all the items raised on their intention to use ICT for teaching and there is no significant difference between male and female Basic Technology teachers on the intention to use ICT tools for teaching. The study concluded that Basic Technology teachers’ intention to use ICT for teaching were positive and there is no significant difference between male and female Basic Technology teachers on the intention to use ICT tools for teaching. The study recommends that Basic Technology teachers should endeavor to give the students activities that will involves the use of ICT since they have positive intention to use ICT.